Typhoid Fever in Children - Soelistyowati S.; Yati Soenarto; Hafni Soesilo; Widiarto Widiarto; Widiatmodjo Widiatmodjo; Ismangoen Ismangoen (Indonesian Pediatric Society, 1982)
One hundred ana fifty eight cases of Typhoid fever in children are reported as a result of a one year study.Blood Salmonella typhi culture was found in 52.3%, wheereas Widal titer was positive in 57.9% cases. Fever and aneosinophilia were found in all of the 158 patients (100%), While 76.3% had constipation, 59.5% disturbance of consciousness, 98% leucopenia and 33.3% diarrhoea occurring in children below 5 years.The result of treatment with chloramphenicol 75 mg/ kg Bw/day showed that the body temperature retumed to normal in an average of 4.9 days after theÂ administration of the drug, whereas hospitalization lasted 14.4 days (average). Three patents (/.9o/o) died because of perforation :and bronchopneumonia and 5 failures were considered as caused by drug relsistancy.During this study the typhoid fever morbidity rarte in the hospital was 8.1% with the case fatality r.ate as high Â·as 1.6%. The higr.est outbreak happened at the beginning of the rainy season.